Global Scaling Up Handwashing Project : Involving Men in Handwashing Behavior Change Interventions in Senegal - World Bank (Washington, DC, 2012)
Launched in December 2006, the Water and Sanitation Program (WSP) Global Scaling up Handwashing Project has been implemented by local and National governments in Peru, Senegal, Tanzania, and Vietnam, with technical support from WSP. A central component of the handwashing project is the planning and implementation of an integrated communications program that includes mass media at national and local levels and community promotional events, led by private firms skilled in experiential marketing and advertising. In addition, interpersonal communications at the household level is handled by fieldworkers (called relays in Senegal) who have previously worked on other public health issues such as family planning, nutrition, and HIV/AIDS prevention. The main responsibility of the relays is to reach out to the households and convince mothers to set up designated areas for handwashing (i.e., handwashing stations) to provide convenient access to soap and water when and where needed.